THE IMPORTANCE OF TRAINING AND EMPLOYEE DEVELOPMENT FOR ORGANIZATIONAL EFFICIENCY - Matejić, Ivica; Ćurčić, Mihailo (Ekonomija - teorija i praksa, 2023)
Given the growing importance and role of human resource management, it is necessary to underline the importance of training and continuous development of employees for organizational development. When it comes to the claim that the employee is the most important resource of a company, it is necessary to actively study the scientific spheres that with their ideas and discoveries can contribute to improving all aspects of the work process. Training is one of the steps in this process, and their successful mastering is a prerequisite for achieving the principle of efficiency. The scientific goal of this research is the scientific description and scientific explanation of the elements, functional factors, and steps necessary for the improvement of the employed staff, with a special emphasis on their training and development in a given social context. The social goal of this research is to present the role and importance of the development and training of employees, as well as the usefulness of the existence of these methods and instruments for human resource management and organizational development in general, on the example of the conducted research.